Uncompensated grain boundary spin driven exchange bias effect in granular NiO film. (August 2019) - Das, S.; Giri, N.; Sarkar, S.; Mondal, A.; Majumdar, S.; Giri, S.; Ray, R.
Abstract: Significant exchange bias effect has been identified in the granular Nickel oxide (NiO) film prepared by sol-gel dip-coating technique on a silicon wafer substrate. Atomic force microscopy displays grain sizes in the range 15–25 nm. Thermal variation of zero field cooled magnetization (ZFC) measured in 500 Oe shows a broad peak around 156 K. Below 25 K, both field cooled (FC) and ZFC magnetization display a significant rise indicating existence of a ferromagnetic (FM) component, which is suggested due to the uncompensated (UC) spins residing at the grain boundaries. The systematic shift in the magnetic hysteresis loops are observed when the sample is field cooled. The shift is the manifestation of exchange bias effect (EB). Training effect is observed at 6 K which could be analyzed by a recursive formula in the framework of spin configurational relaxation model. We propose that pinning mechanism at the interface between antiferromagnetic core and shell consisting of uncompensated spins leads to the EB effect in the granular NiO film. Highlights: NiO film is prepared from sol-gel dip coating technique. Significant exchange bias is observed at low temperature. Surface anisotropy of uncompensated spin causes exchange bias.